Estudo prospectivo de fase ½ para avaliação da maior dose tolerável, toxicidade, farmacocinética e eficácia do LDE-etoposide no condicionamento do transplante alogênico de células-tronco hematopoeticas de pacientes com leucemia mieloide aguda recaída / refratária. - Rohr, Sandra Serson [UNIFESP] (2018)
acute myeloid leukemia (AML) is a disease that requires intensive treatment. Allogeneic hematopoietic stem cell transplantation (HSCT) is curative for many patients with AML and is indicated in relapsed or refractory (R/R) AML. Innovative experiments demonstrated that artificial, nonliposomal, LDL-simile nanoparticles, termed LDE, concentrate in myeloid blastic cells. The association of etoposide to LDE (LDE-etoposide) was studied aiming the improvement of its antileukemic effect. Purpose: Test dose-escalating of LDE-etoposide in the conditioning regimen of related or unrelated allogeneic HSCT of patients with the diagnosis of R/R AML, explore the toxicity profile of LDE-etoposide, study the pharmacokinetics of LDE-etoposide, evaluate the efficacy of LDE-etoposide in the conditioning regimen of HSCT of R/R AML patients and assess the overall survival and event-free survival of these patients. Methods: Patients with R/R AML were prospectively submitted to myeloablative HSCT. The day of stem cell infusion was defined as D0. The conditioning regimen plan consisted of dose-escalating I.V. infusion of total LDE-etoposide on days -7 and -6 and fractioned total body irradiation (1200cGy) from days -3 to -1. In the case of unrelated donors, patients also received thymoglobulin. Graft versus-host-disease (GVHD) prophylaxis consisted of cyclosporine and methotrexate. Results: Total 15 R/R AML patients, 8 males and 7 females, aged 22-66 yrs. (median 47 yrs.) underwent HSCT in 2 centers. LDE-etoposide dose was escalated from 20 mg/kg BW until 60 mg/kg BW. During the infusion of the LDEetoposide preparation, no episodes of hypotension, anaphylaxis, bronchospasm or other adverse effects occurred. Engraftment failure did not occur. Neutrophil and platelets engraftment occurred on (20 ± 4.9) days and 16 ± 3 days (medianSD) respectively. Only few occurrences of major (grades 3 and 4) toxicities were registered and no fatal events occurred that could be ascribed to toxicity of the treatment. Only one patient presented grade 4 mucositis and 5 patients grade 3 mucositis. It is worth mentioning the near total absence of sinusoidal obstruction syndrome (SOS). No cases of severe acute graft-versus-host-disease (aGVHD) occurred and four patients presented only mild aGVHD. The incidence of chronic GVHD, 27% in severe form and 27% in moderate form, was roughly within the frequency reported in the literature. Among the 15 treated patients, five died, only one before D100. Death occurred after engraftment, and was caused by hypertensive crisis leading to pneumothorax. Three patients died because of refractory disease and one patient died of relapsed disease. Three patients are currently treating relapsed disease and seven patients are in complete response with 100% chimerism. Overall survival of the study patients, estimated by Kaplan-Meier, was 64% and event-free survival (death or relapse) 42.7%, both in 2.3 years. Total plasma cholesterol as measured before and around 100 days after HSTC increased 14% (p<0.05) in accordance with the literature report of AML patients in hematological remission. The mean-time follow-up was 18 months (range 4 - 28). Conclusion: this study shows the benefits to RR AML patients of this novel strategy in which a drug targeting system (LDE) was used for the first time in HSCT. Extremely low toxicity, absence of SOS, very low occurrence of acute GVHD, no deaths related to the conditioning regimen and the 64% two-year survival were hallmarks of this novel approach that has clear potential to be advantageously introduced into clinical practice.